Formation Of Kazakhstan As A Secular State: Legal Aspects - Balgabay Nakipov, Maksat Moldaliev, Daulet Kozhambekov, Nurlan Batyrbaev,; Alayeva, Gulnaz (Opción, 2019)
The aim of the study is to investigate the legal aspects of the formation of Kazakhstan as a secular state. The structure of the study is expressed in the standard observational descriptive analysis of the mandatory components of secularity. In result, one can recognize a certain kind of sanction against officials of a legally registered religious association to influence the state. In conclusion, by interfering in the livelihoods of religious associations, the state, for its part, does not, in any way, affect the choice in the religion of citizens, which, indirectly corresponds to the principles of secularism of the state.